Medico-Legal Evaluation of Adult Female Sexual Assault Survivors: A Retrospective Study of Evidence, Clinical History and Gynecological Implications - Aisha Rasheed, Asiya Parveen, Shahzad Ahmadani, Araj Hussain, Ishrat Bibi, Samina, Abdul Samad, Marvi, (Pakistan Journal of Medical & Health Sciences, 2024)
Introduction: Sexual assault involves non-consensual physical or sexual contact, causing harm to the victim. In such cases, healthcare professionals in emergency departments play a critical role as they are often the first point of contact for victims. Effective management of these cases relies heavily on proper evidence sampling, which is crucial for identifying perpetrators. However, in Pakistan, the low conviction rate in sexual assault cases is often attributed to inadequate forensic sampling techniques and a lack of specialized expertise, highlighting the need for improved training and protocols. Objectives This study investigates sexual assault cases among women, focusing on prevalence, management and impacts. Method: The study was conducted at Department of Forensic Medicine & Toxicology, LUMHS, Jamshoro and Medicolegal Section, Liaquat University Hospital, Hyderabad, analyzing data from July 2022 to June 2023. It identified 80 cases of female sexual assault victims who underwent comprehensive medical examinations by female medical officers. Biological samples, including vulvar, vaginal, and rectal swabs, were collected from the victims as part of the examination process. Results: The results showed 80 cases of female sexual assault victims. The victims' ages ranged from 15 to 40 years, with a mean age of 22.4 years (±3.12 years). Notably, 67% of the victims were unmarried and 65.1% belonged to lower socioeconomic backgrounds. Furthermore, 72.1% of the victims reported a history of penetration. Laboratory analysis of samples from these victims revealed that only 40% of those with a penetration history tested positive for male DNA. Conclusion: Pakistan's healthcare system requires improvement, particularly in emergency departments, to effectively manage sexual assault cases. Healthcare professionals need training to properly collect and handle forensic evidence, record victim histories and document medical reports. Specialized forensic training is crucial for identifying perpetrators. Additionally, awareness campaigns in rural areas can educate communities about sexual assault and its long-term effects, promoting support for survivors and prevention efforts. Keywords: Sexual assault, Forensic sampling, female victims, Survivors